2016
DOI: 10.1111/izy.12116
|View full text |Cite
|
Sign up to set email alerts
|

Causes and prevention of foot problems in Greater one‐horned rhinoceros Rhinoceros unicornis in zoological institutions

Abstract: Greater one‐horned rhinoceros Rhinoceros unicornis have been successfully maintained by and bred at zoological gardens in the past half century. Despite this success, decades ago it was recognized that this species frequently develops foot lesions. Such damage can impair the health and well‐being of an individual, and contribute to a reduction of its lifespan. The death of a breeding bull or cow will have an effect upon the success of the breeding programme. Various studies have been carried out to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Obesity is considered a contributing factor once the disease is established, delaying the healing of the affected feet. At one facility with very intensive monitoring of foot health, an improvement and prophylactic effect with a change from hard substrate to a deep layer of woodchips in both the indoor and outdoor enclosure was observed [von Houwald, 2016], and a different questionnaire than the one used in the present study, filled in by eight zoological institutions, indicated fewer foot problems in those facilities that had instigated similar changes [von Houwald, 2016]. By contrast, in the present study, BCS and enclosure characteristics (such as the proportion of soft and hard substrate) did not differ for animals without and with mid-to long-term foot problems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Obesity is considered a contributing factor once the disease is established, delaying the healing of the affected feet. At one facility with very intensive monitoring of foot health, an improvement and prophylactic effect with a change from hard substrate to a deep layer of woodchips in both the indoor and outdoor enclosure was observed [von Houwald, 2016], and a different questionnaire than the one used in the present study, filled in by eight zoological institutions, indicated fewer foot problems in those facilities that had instigated similar changes [von Houwald, 2016]. By contrast, in the present study, BCS and enclosure characteristics (such as the proportion of soft and hard substrate) did not differ for animals without and with mid-to long-term foot problems.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pododermatitis (CP) is a multifactorial disease, where suboptimal husbandry (especially inadequate flooring and a lack of pools) is probably the most influential etiologic factor, as this condition is not described in free‐ranging animals and the incidence in the captive population is high; cracks, non‐healing fissures, ulcers between the sole of the central toe and the adjacent pad, and pad overgrowth characterize this condition [von Houwald, , ; Atkinson et al, ]. Obesity is considered a contributing factor once the disease is established, delaying the healing of the affected feet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to control the parasitic load, the rhinoceros were kept inside on concrete substrates and easy‐to‐clean floors were provided outside. Unfortunately, this type of hard substrate led to the occurrence of foot problems (von Houwald & Flach, ; von Houwald, ). Bulls suffered from severe foot problems and, as a consequence, some of them died at a young age (14–20 years), which led to a loss of breeding bulls in the captive population (von Houwald, ).…”
Section: Husbandrymentioning
confidence: 99%